Relationship between occupational stress, emotional intelligence and job performance: An empirical study in Malaysia - Ismail, Azman; Yeo, Suh-ssuh; Ajis, Mohd Na'eim; Dollah, Noor Faizah (General Association of the Economists in Romania (AGER), 2009)
This study was conducted to examine the effect of emotional intelligence in the relationship between occupational stress and job performance using 104 usable questionnaires gathered from academic employees who work in private institutions of higher learning in Kuching City, Malaysia. The outcomes of testing research hypothesis using a stepwise regression analysis showed that relationship between occupational stress and emotional intelligence significantly correlated with job performance. Statistically, the result confirms that the inclusion of emotional intelligence in the analysis has mediated the effect of occupational stress on job performance in the organizational sector sample.Further, implications and discussion are elaborated.